Case Report: Surgical treatment of lumbar ligamentum flavum cysts combined with spinal instability causing radiculopathy - Yang, Keshi; Ji, Changbin; Luo, Dawei; Yin, Jiwei; Wu, Xiaozhe; Xu, Hui (Frontiers in Surgery, 2025)
PurposeThis study aimed to describe a case of a patient with a lumbar ligamentum flavum cyst combined with spinal instability who underwent cyst resection and transforaminal lumbar interbody fusion (TLIF).MethodsWe present a rare case of a patient with a lumbar ligamentum flavum cyst combined with spinal instability causing radiculopathy. The patient underwent cyst resection and transforaminal lumbar interbody fusion.ResultsThe patient underwent follow-up for 3 years postoperatively and remained asymptomatic, with favorable radiographic results.ConclusionsCysts resection and TLIF for ligamentum flavum cysts combined with spinal instability can achieve sufficient and effective decompression while simultaneously restoring spinal stability. Therefore, this approach is both an effective and safe treatment option.